(untitled) - D. Asmat-Campos; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The COVID-19 pandemic is devastating in many countries. Despite countless global containment and quarantine efforts, the death toll continues to rise. This manuscript aims to comment on the specific case of Peru, the first country in Latin America where the government adopted drastic containment measures. However, a series of social factors continue to affect its current status as the country with the second-highest number of infections in the Americas and the fifth in the world (as of June end).